PARTISIPASI PEREMPUAN DALAM PROSES PEMBUATAN PARAREM DI DESA PAKRAMAN PANJER, KECAMATAN DENPASAR SELATAN, KOTA DENPASAR - Yuda Krisna, I Wayan; Dewi Pascarani, Ni Nyoman; Winaya, I Ketut (CITIZEN CHARTER, 2015)
ABSTRACT Participation is manifestation from Governance characterized for through best performance by government. Once of manifestation from society participation is the involvement from women whose making Pararem from Desa pakraman. There is like women activity in Desa Pakraman Panjer, Kecamatan Denpasar Selatan whose made they have rights for giving their opinions. With this problems patterns, this research is aim for knowing how far the participation from women within process for making Pararem in Desa Pakraman Panjer, Kecamatan Denpasar Selatan. This research using descriptive qualitative method through collect the data from direct observation for looking the phenomenon and doing interview with interviewees which involving in makin Pararem in Desa Pakraman Panjer, Kecamatan Denpasar Selatan. This research conclude, the woman involvement in process for making Pararem just giving their opinions like talking about something which they want or adding in Pararem. Within the process for making Pararem can be found four phases which planning phase, framing phase, ratification phase and socialization phase. The women involvement in process for making Pararem just can be found in planning phase, and socialization phase. The women involvement can be seen in process from making Pararem which related with women’s right and obligations in Upakara things, while they have asked about their opinions but the framing phase is doing by men. Keywords : Participation, Pararem, Desa Pakraman, Women